The relationship between physical activity and trait anxiety in college students: The mediating role of executive function - Dong, Zhiwei; Wang, Peng; Xin, Xin; Li, Shufan; Wang, Jing; Zhao, Jinlei; Wang, Xing (Frontiers in Human Neuroscience, 2022)
Objectives Aimed to analyze the mediating effect of executive function between physical activity level and trait anxiety in college students. Methods The International Physical Activity Questionnaire, State-Trait Anxiety Inventory, Stroop task, 1-back task, and More-odd shifting task were used to analyze 248 college students. Results Trait anxiety were significantly correlated with shifting function (r = 0.182, P = 0.004) and inhibition function (r = 0.163, P = 0.010) and not with working memory (r = 0.056, P = 0.385). Vigorous physical activity (VPA) was most highly correlated with inhibition function (Beta = −0.144, P = 0.024) and working memory (Beta = −0.208, P = 0.001), and light physical activity (LPA) was most highly correlated with shifting function (Beta = −0.211, P = 0.001). Physical activity had a 72.31% association with trait anxiety (B = −0.195), with 11.79% mediated by inhibition function (B = −0.023) and 15.90% by shifting function (B = −0.031). Conclusion College students' physical activity promotes both inhibition and shifting functions, which in turn affect trait anxiety. VPA had a direct effect, while the effect of moderate physical activity (MPA) and LPA was completely mediated exclusively through executive functions, and the mediating effect of shifting function was the highest. It is recommended that college workers should motivate students with high trait anxiety to engage in more VPA and pay attention to changes in their inhibition and shifting functions.